Strategic Framing in Tax Communication: Reconsidering Policy Narratives Through Justice-Based Approaches - Fitriyah, Aidatul; Nasrulloh, Ubaid Fandi (Yayasan Sinergi Kawula Muda, 2025)
This study explores the framing effects in tax policy communication and how they influence public perception, compliance behavior, and institutional trust across various political and cultural contexts. Framing refers to the strategic presentation of tax messages, which can significantly shape public understanding and attitudes. A structured narrative review was employed, synthesizing key empirical and theoretical contributions using targeted keyword searches across multiple databases, but without formal coding protocols as in a systematic review. Key search terms included